Elefantes, instituições e ciência nas fraturas coloniais - Campos, Ana Cecília Oliveira (2024)
This dissertation is an ethnography of the relationship between humans and elephants, focusing on the intertwining of environmental and colonial issues. The research describes four different contexts: the first sanctuary for elephants in South America, a National Park in Mozambique, a zoo in Argentina and a zoo in Brazil. The ethnographic strategy was to follow elephants in their movements along sanctuary and zoo fences, in scientific articles, in institutional and legal documents and in the reports of interlocutors who consider elephants as companion species. On the one hand, these different materials show multispecies assemblies in which keepers, veterinarians, lawyers, institutions and donors come together around elephants and their life stories. On the other hand, it explains the historical relationship between elephants as a symbol of colonial triumph, which is seen both in the relationship between zoos and the colonial trade in exotic species and in the behavior of herds that still deal with the traumatic memories of hunting. Highlighting this intertwining has the political importance of situating multispecies ethnographies not only in relation to the plantationcene, but also in relation to the theme of raciality as a historical referent of multispecies relations and as a potential tool for rethinking engagements in anthropological practice.